Hemodynamic Monitoring of Transcatheter Closure in Patients with Patent Foramen Ovale: A Case Study - Julianthi, Anita; Nurhayati, Nurhayati; Oemar, Hamed (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2025)
Patent Foramen Ovale (PFO) is a congenital cardiac anomaly characterized by the persistent opening of the foramen ovale, resulting in a right-to-left shunt due to incomplete closure of the interatrial septum after birth. Incidences of PFO is about 25% or 1 in 4 people in the world's population. Methods: this case study aimed to assess hemodynamic changes during transcatheter closure of PFO in an adult patient. The procedure was monitored for changes in ECG, pulse rate, and blood pressure, highlighting potential risks such as puncture wounds. Findings suggest that comprehensive hemodynamic monitoring is essential during PFO closure procedures. A 66 years old man with a history of symptoms of slurred speech symptoms staggering and then fainting then the PFO closure that is taken during disease management during January - May 2024 at RSUPN Dr. Cipto Mangunkusumo (RSCM). Results: during the PFO Closure procedure, there were changes in the ECG rhythm from Sinus Rhythm to PVC Rythm, decrease pulse rate, decrease in the patient's blood pressure from 176/89 to 118/78 mmHg, as well as risks such as puncture wounds. Conclusion: hemodynamic monitoring during transcatheter closure of Patent Foramen Ovale (PFO) is crucial to detect potential changes and complications. Close surveillance is necessary to identify and promptly manage procedural risks.